تأثير عمليات ادارة الموهبة في المنظمات الريادية دراسة استطلاعية لآراء عينة من مديري شركة كورك للاتصالات المتنقلة - أحمد عبد الله أمانة الشمري; لمياء علي ابراهيم الموسوي; سرمد عبد الله امانة الشمري (مجلة الغري للعلوم الاقتصادية والادارية)
المستخلص سعى هذا البحث إلى تحدید تأثیر عملیات ادارة الموهبة في المنظمات الریادیة بالتطبیق في منظماتنا الع ا رقیة ومن أجل تحقیق ذلك تم اعتماد أبعاد (عملیات) ادارة الموهبة (استقطاب الموهبة، اختیار الموهبة، كما تم اعتماد أبعاد ،(Phillips, تطویر الموهبة، المحافظة على الموهبة) استنادا إلى ( 2009:10 المنظمات الریادیة (الاستقلالیة، الإبداعیة، الاستباقیة، تحمل المخاطرة) بالاستناد إلى مجموعة من الكتاب تم اختیار شركة كورك للاتصالات المتنقلة میداناً للبحث ،(Dess,etal., والباحثین ومنهم ( 2008:434 من خلال استمارة استبانه شملت ( 30 ) فرداً من مدیري فروع الشركة، فضلاً عن المقابلات الشخصیة. وقد (F) لمعرفة معنویة العلاقة بین المتغی ا رت، واختبار (t) واختبار ،(Spearman) استخدم معامل الارتباط لتفسیر مقدار تأثیر المتغیر المستقل في المتغیر (R لتحدید معنویة معادلة الانحدار، كما تم استخدام( 2 التابع. ومن أهم الاستنتاجات التي تم التوصل إلیها هو إن لعملیات إدارة الموهبة دو ا رً فاعلاً في وصول المنظمات للریادیة. Abstract This Research aimed at determining the Impact of Talent Management Process on the Entrepreneurial Organizations for Iraqi Organizations. For this purpose the researcher has depended on the dimensions (Process) of Talent Management (Talent Recruitment, Talent Selecting, Talent Development, and Retention the Talent) according to (Phillips,2009:10). The dimensions of Entrepreneurial Organizations (Autonomy, Innovativeness, Proactiveness & Risk Taking) that have been used according to(Dess,etal,2008:434). The Korek Company for Communications has been chosen to verify this Research via a questionnaire used (30) individuals of the managers of the company, in addition to personal interviews. The Spearman connection factor and the (t) test to recognize the identity of this relation, and the (F) test to determine the identity of the regression equation, also the (R2) has been used to explain the degree of the influence of the independent variable in the dependent variable. Some of the most important conclusions the study arrived at are that Talent Management Process have active role on Arriving Organization to Entrepreneurship.